Correction to: Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI (European Radiology Experimental, (2023), 7, 1, (80), 10.1186/s41747-023-00394-1) - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2024)
The original article [1] omits the following funding information that the authors would like to note in this correction article: “We acknowledge financial support by Deutsche Forschungsgemeinschaft and Friedrich-Alexander-Universität Erlangen-Nürnberg within the funding programme "Open Access Publication Funding".”.
CRIS-Team Scopus Importer:2024-03-22

Free-Breathing Low-Field MRI of the Lungs Detects Functional Alterations Associated With Persistent Symptoms After COVID-19 Infection. - Levy, Simon; Heiß, Rafael; Grimm, Robert; Grodzki, David; Hadler, Dominique; Voskrebenzev, Andreas; Vogel-Claussen, Jens; Fuchs, Florian; Strauss, Richard; Achenbach, Susanne; Hinsen, Maximilian; Klett, Daniel; et al. (Investigative Radiology, 2022)
OBJECTIVES: With the COVID-19 pandemic, repetitive lung examinations have become necessary to follow-up symptoms and associated alterations. Low-field MRI, benefiting from reduced susceptibility effects, is a promising alternative for lung imaging to limit radiations absorbed by patients during CT examinations, which also have limited capability to assess functional alterations. The aim of this investigative study was to explore the functional abnormalities that free-breathing 0.55 T MRI in combination with the phase-resolved functional lung (PREFUL) analysis could identify in patients with persistent symptoms after COVID-19 infection. MATERIALS AND METHODS: Seventy-four COVID-19 patients and 8 healthy volunteers were prospectively scanned in free-breathing with a balanced steady-state free-precession sequence optimized at 0.55 T, 5 months postinfection on average. Normalized perfusion (Q), fractional ventilation (FV), and flow-volume loop correlation (FVLc) maps were extracted with the PREFUL technique. Q, FV, and FVLc defects as well as defect overlaps between these metrics were quantified. Morphological turbo-spin-echo images were also acquired, and the extent of abnormalities was scored by a board-certified radiologist. To investigate the functional correlates of persistent symptoms, a recursive feature elimination algorithm was applied to find the most informative variables to detect the presence of persistent symptoms with a logistic regression model and a cross-validation strategy. All MRI metrics, sex, age, body mass index, and the presence of preexisting lung conditions were included. RESULTS: The most informative variables to detect persistent symptoms were the percentage of concurrent Q and FVLc defects and of areas free of those defects. A detection accuracy of 71.4% was obtained with these 2 variables when fitting the model on the entire dataset. Although none of the single variables differed between patients with and without persistent symptoms ( P > 0.05), the combined score of these 2 variables did ( P < 0.02). This score also showed a consistent increase from healthy volunteers (7.7) to patients without persistent symptoms (8.2) and with persistent symptoms (8.6). The morphological abnormality score showed poor correlation with the functional parameters. CONCLUSIONS: Functional pulmonary examinations using free-breathing 0.55 T MRI with PREFUL analysis revealed potential quantitative markers of impaired lung function in patients with persistent symptoms after COVID-19 infection, potentially complementing morphologic imaging. Future work is needed to explore the translational relevance and clinical implication of these findings.
EVALuna2:506323

Hattori-Zyste – eine seltene Läsion im posterioren Mediastinum - Elsner, Felix; Khamitov, Koblandy; Hinsen, Maximilian; Sirbu, Horia; Hartmann, Arndt (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Lungenbildgebung in der Niederfeld-Magnetresonanztomographie - Hinsen, Maximilian; Heiß, Rafael; Nagel, Armin Michael; Levy, Simon; Uder, Michael; Bickelhaupt, Sebastian; May, Matthias (Radiologe, 2022)
Background: Lung magnetic resonance imaging (MRI) examinations are challenging and have not become established in the routine clinical setting. Recent developments in low-field MRI, combined with computer-assisted algorithms for acquisition and evaluation, promise new perspectives for imaging of pulmonary diseases. Objectives: This review aims to inform about the physical advantages of low-field MRI for imaging the lungs, provide a review of the sparse literature, and present first results from a new low-field MRI scanner. Materials and methods: This article provides information on the physical principles, an review of the literature, and our first experiences in lung imaging on a modern 0.55 T MRI. Conclusion: Low-field MRI (< 1 T) may have technical and economic advantages over higher field strength MRI in lung imaging. The physical preconditions of low-field MRI are advantageous for imaging the lungs due to reduced susceptibility effects, increased transversal relaxation times, and lower specific absorption rates. The lower investment and operating costs may enable increased availability and sustainability. Combining modern sequences and computer-based image processing may expand beyond morphological imaging by providing spatially and temporally resolved functional examinations of the lung parenchyma without ionizing radiation. In critical scenarios, like screening and short-term follow-up examinations, and patients at risk, low-field MRI may bridge the gap. These indications may include acute and chronic pulmonary diseases in pediatric patients and suspected pulmonary embolisms in pregnant women.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Field strength; Functional analysis; Image quality; Low-field system; Lung imaging

Lungenbildgebung in der Niederfeld-Magnetresonanztomographie - Hinsen, Maximilian; Heiß, Rafael; Nagel, Armin Michael; Levy, Simon; Uder, Michael; Bickelhaupt, Sebastian; May, Matthias (Zeitschrift für Pneumologie, 2024)
Background: Lung magnetic resonance imaging (MRI) examinations are challenging and have not become established in the routine clinical setting. Recent developments in low-field MRI, combined with computer-assisted algorithms for acquisition and evaluation, promise new perspectives for imaging of pulmonary diseases. Objectives: This review aims to inform about the physical advantages of low-field MRI for imaging the lungs, provide a review of the sparse literature, and present first results from a new low-field MRI scanner. Materials and methods: This article provides information on the physical principles, an review of the literature, and our first experiences in lung imaging on a modern 0.55 T MRI. Conclusion: Low-field MRI (< 1 T) may have technical and economic advantages over higher field strength MRI in lung imaging. The physical preconditions of low-field MRI are advantageous for imaging the lungs due to reduced susceptibility effects, increased transversal relaxation times, and lower specific absorption rates. The lower investment and operating costs may enable increased availability and sustainability. Combining modern sequences and computer-based image processing may expand beyond morphological imaging by providing spatially and temporally resolved functional examinations of the lung parenchyma without ionizing radiation. In critical scenarios, like screening and short-term follow-up examinations, and patients at risk, low-field MRI may bridge the gap. These indications may include acute and chronic pulmonary diseases in pediatric patients and suspected pulmonary embolisms in pregnant women.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Field strength; Functional analysis; Image quality; Low-field system; Lung imaging

Lung Nodule Detection With Modern Low-Field MRI (0.55 T) in Comparison to CT. - Hinsen, Maximilian; Nagel, Armin M.; May, Matthias; Wiesmüller, Marco; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2024)
OBJECTIVES: The aim of this study was to evaluate the accuracy of modern low-field magnetic resonance imaging (MRI) for lung nodule detection and to correlate nodule size measurement with computed tomography (CT) as reference. MATERIALS AND METHODS: Between November 2020 and July 2021, a prospective clinical trial using low-field MRI at 0.55 T was performed in patients with known pulmonary nodules from a single academic medical center. Every patient underwent MRI and CT imaging on the same day. The primary aim was to evaluate the detection accuracy of pulmonary nodules using MRI with transversal periodically rotated overlapping parallel lines with enhanced reconstruction in combination with coronal half-Fourier acquired single-shot turbo spin-echo MRI sequences. The secondary outcome was the correlation of the mean lung nodule diameter with CT as reference according to the Lung Imaging Reporting and Data System. Nonparametric Mann-Whitney U test, Spearman rank correlation coefficient, and Bland-Altman analysis were applied to analyze the results. RESULTS: A total of 46 participants (mean age ± SD, 66 ± 11 years; 26 women) were included. In a blinded analysis of 964 lung nodules, the detection accuracy was 100% for those ≥6 mm (126/126), 80% (159/200) for those ≥4-<6 mm, and 23% (147/638) for those <4 mm in MRI compared with reference CT. Spearman correlation coefficient of MRI and CT size measurement was r = 0.87 ( P < 0.001), and the mean difference was 0.16 ± 0.9 mm. CONCLUSIONS: Modern low-field MRI shows excellent accuracy in lesion detection for lung nodules ≥6 mm and a very strong correlation with CT imaging for size measurement, but could not compete with CT in the detection of small nodules.
EVALuna2:549646

Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2023)
Background: To analyze regional variations in T2 and T2* relaxation times in wrist joint cartilage and the triangular fibrocartilage complex (TFCC) at 3 and 7 T and to compare values between field strengths. Methods: Twenty-five healthy controls and 25 patients with chronic wrist pain were examined at 3 and 7 T on the same day using T2- and T2*-weighted sequences. Six different regions of interest (ROIs) were evaluated for cartilage and 3 ROIs were evaluated at the TFCC based on manual segmentation. Paired t-tests were used to compare T2 and T2* values between field strengths and between different ROIs. Spearman’s rank correlation was calculated to assess correlations between T2 and T2* time values at 3 and 7 T. Results: T2 and T2* time values of the cartilage differed significantly between 3 and 7 T for all ROIs (p ≤ 0.045), with one exception: at the distal lunate, no significant differences in T2 values were observed between field strengths. T2* values differed significantly between 3 and 7 T for all ROIs of the TFCC (p ≤ 0.001). Spearman’s rank correlation between 3 and 7 T ranged from 0.03 to 0.62 for T2 values and from 0.01 to 0.48 for T2* values. T2 and T2* values for cartilage varied across anatomic locations in healthy controls at both 3 and 7 T. Conclusion: Quantitative results of T2 and T2* mapping at the wrist differ between field strengths, with poor correlation between 3 and 7 T. Local variations in cartilage T2 and T2* values are observed in healthy individuals. Relevance statement: T2 and T2* mapping are feasible for compositional imaging of the TFCC and the cartilage at the wrist at both 3 and 7 T, but the clinical interpretation remains challenging due to differences between field strengths and variations between anatomic locations. Key points: •Field strength and anatomic locations influence T2 and T2* values at the wrist. •T2 and T2* values have a poor correlation between 3 and 7 T. •Local reference values are needed for each anatomic location for reliable interpretation. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-22
Keywords: Cartilage (articular); Image processing (computer-assisted); Magnetic resonance imaging; Triangular fibrocartilage; Wrist joint